Confined voltage stabilizers into hard segment of polyurethane for soft dielectric elastomers with enhanced electroactuation performance - Xiao, Youhua; Hu, Ruifeng; Li, Jiahao; Ni, Jingwen; Yu, Xiao; Lu, Xiaodong; Shang, Xingyu; Mao, Jie; Yang, Shengxiang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Dielectric elastomer (DE) materials hold promise as artificial muscles due to their ability to deform under external electric field stimulation. To enhance their actuation performance, we have improved the dielectric breakdown strength of polyurethane (PU) based DE materials by incorporating voltage stabilizers into their hard segment through copolymerization. Voltage stabilizers with a lower HOMO-LUMO energy gap can effectively capture high-energy electrons, thereby mitigating the degradation of polymer molecular chains and increasing the dielectric breakdown strength. Specifically, when 50 % of the hard segments in PU contain a kind of voltage stabilizer (4,4′-dihydroxybenzophenone, DHBP), the PU exhibits the optimized dielectric breakdown strength, increasing from an initial value of 32 V/μm to 58 V/μm. Notably, the modified PU retains a low initial modulus (0.24 MPa) without experiencing the stiffening problem, as the rigid structure of the DHBP is incorporated into the hard segments of PU. Without pre-stretching, the 50 % DHBP-PU achieves an improved maximum actuation strain of 57 % and a theoretical energy density of 14.4 J/m3 at 83 V/μm, outperforming most PU-DE materials. The DHBP-PU, characterized by its enhanced dielectric breakdown strength and improved electroactuation performance, holds great potential for applications in flexible actuators and soft robotics. •Dielectric breakdown strength of PU-DEs can be improved by incorporating DHBP, a voltage stabilizer with lower HOMO-LUMO gap.•Incorporating rigid DHBP into hard segments of PU can prevent serious stiffening problems, ensuring the material softness.•When 50% of hard segments contain DHBP, the breakdown strength of actuation of PU-DEs increases from 32 V/μm to 58 V/μm.•Improving the dielectric breakdown strength of DE materials is crucial for improving the electroactuation performance.